Dynamic changes of cytokine profiles and virological markers during 48 weeks of entecavir treatment for HBeAg-positive chronic hepatitis B - Li, Minghui; Gao, Yuanjiao; Yang, Liu; Lin, Yanjie; Deng, Wen; Jiang, Tingting; Bi, Xiaoyue; Lu, Yao; Zhang, Lu; Shen, Ge; Liu, Ruyu; Wu, Shuling; et al. (Frontiers in Immunology, 2022)
Objective The aims of this study were to investigate the kinetic changes of serum, virological, and immunological markers during entecavir (ETV) antiviral therapy and to explore whether these indicators can predict the antiviral efficacy of ETV in hepatitis B e antigen (HBeAg)-positive chronic hepatitis B (CHB) patients. Methods HBeAg-positive CHB patients were enrolled and treated with ETV 0.5 mg/day. Clinical biochemical, virological, and serological tests were performed at baseline and every 12 weeks during the 48-week treatment. Plasma levels of cytokines (Flt-3L, IFN-α2, IFN-γ, IL-10, IL-17A, IL-6, TGF-β1, TGF-β2, TGF-β3, and TNF-α) were measured at baseline and at 12 and 24 weeks after treatment. Analysis of the trends of these clinical indicators in ETV antiviral therapy was performed. Results A total of 105 HBeAg-positive CHB patients were enrolled, and 100 of them completed 48 weeks of ETV treatment and follow-up. After 48 weeks of treatment, hepatitis B s antigen (HBsAg) decline ≥ 1 log10 was found in seven patients, but no patient achieved HBsAg disappearance. serological HBeAg disappeared in 13 patients, and serological HBeAg transformed in 3 patients. The baseline HBsAg and HBeAg levels, HBV DNA load, IL-10, and TGF-β1 levels in the complete virological response group were lower than those in the incomplete virological response group, while the ALT level in the complete virological response group was higher than that in the incomplete virological response group. Both univariate analysis and multivariate analysis showed that baseline biochemical indexes, virological indexes, and cytokine levels had no correlation with the complete virological response at 48 weeks. In multivariate analysis, low baseline HBV DNA load, and HBeAg and IL-10 levels were significantly associated with ALT normalization after 48 weeks of ETV treatment (HBeAg OR = 1.003, 95% CI 1.001–1.006, p = 0.007; HBV DNA OR = 0.184, 95% CI 0.046–0.739, p = 0.017; IL-10 OR = 0.040, 95% CI 0.972–0.999, p = 0.040). Conclusion Cytokine levels changed dynamically during ETV antiviral therapy. Low baseline HBV DNA load, and HBeAg and IL-10 levels were significantly associated with ALT normalization after 48 weeks of ETV treatment.